Laboratory study of the generation of nanoparticles from tire tread. Issue 2 (1st February 2017) - Park, Inyong; Lee, Janghee; Lee, Seokhwan
ABSTRACT: An experimental study was carried out to investigate the formation process of airborne nanoparticles from tire tread. The formation of nanoparticles by volatilization of the tire tread was simulated in a reaction chamber. The number concentration of nanoparticles in the reaction chamber suddenly increased when the tire tread surface temperature reached above 160°C. The generated nanoparticles have a unimodal distribution and the number of nanoparticles increased as the heating rate increased. The geometric mean diameter and size distribution of the generated particles can be controlled by adjusting the cooling rate since the cooling rate is directly related to the growth of particles. From the morphological and elemental analyses, the main components of the tire nanoparticles were C, O, S, and Si and the particles had an irregular shape. Based on these observations, we concluded that the formation mechanism of nanoparticles from the tire tread was volatilization and condensation of the organic materials in the tire tread. Copyright © 2017 American Association for Aerosol Research